Step
*
of Lemma
mFOL-subst-trivial
∀nw,old:ℤ. ∀fmla:mFOL().
  ((¬(old ∈ mFOL-freevars(fmla)))
  
⇒ (mFOL-abstract(fmla[nw/old]) = mFOL-abstract(fmla) ∈ AbstractFOFormula(mFOL-freevars(fmla))))
BY
{ (Auto
   THEN Unfold `mFOL-subst` 0
   THEN (GenConclTerm ⌜mFOL-rename-bound-to-avoid(fmla;[nw])⌝⋅ THENA Auto)
   THEN D -2
   THEN Auto
   THEN InstLemma `trivial-mFOL-rename` []
   THEN Auto) }
Latex:
Latex:
\mforall{}nw,old:\mBbbZ{}.  \mforall{}fmla:mFOL().
    ((\mneg{}(old  \mmember{}  mFOL-freevars(fmla)))  {}\mRightarrow{}  (mFOL-abstract(fmla[nw/old])  =  mFOL-abstract(fmla)))
By
Latex:
(Auto
  THEN  Unfold  `mFOL-subst`  0
  THEN  (GenConclTerm  \mkleeneopen{}mFOL-rename-bound-to-avoid(fmla;[nw])\mkleeneclose{}\mcdot{}  THENA  Auto)
  THEN  D  -2
  THEN  Auto
  THEN  InstLemma  `trivial-mFOL-rename`  []
  THEN  Auto)
Home
Index